SYNTHESIS AND CHARACTERIZATION OF A NEW AMINOPHOSPHAZANE FROM 5-AMINO-1,10-PHENANTHROLINE WITH AMINOLYSIS REACTION - Tuncel Elmali, Fikriye; Atas, Rumeysa; Demirhan, Nebahat (YILDIZ TECHNICAL UNIV, 2007)
In this work a new aminophosphazene, called tris(5-amino-1,10-phenanthrolino)-2,4,6-trichlorocyclo-triphosphazen has been synthesized by the reaction of 5-amino-1,10-phenanthroline with hexachlorocyclotriphosphazene. The structure of the new compound characterized by FTIR, H-1-NMR, P-31-NMR, LC-MS, UV-Vis and fluorescence spectroscopy.
Keywords: Phosphazene; 1,10-phenanthroline; ligand; Engineering